The Relationship between Personality Type and Caring behavioramong ascossiate Nurses at Muhammadiyah Pekajangan Hospital, Pekalongan Regency - Arini Fitriati; Aisyah Dzil Kamalah (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2022)
Background : Nursing is a profession that aims to serve humanity. Nurse-patient interaction involves a professional and therapeutic relationship. The most important in providing nursing services is caring. Caring behaviour is an attitude, care, respect, and respectfor others. The caring behaviour of nurses may be influenced by personality type. Objective : This study aims to determine the relationship between personality type and caring behaviour of nurses. Sample : This study involved all 69 inpatient ward nurses of Muhammadiyah Pekajangan Hospital. Methotds : This descriptive study with a cross-sectional approach was used. Data were collected by using an online questionnaire by google form. Chi-square was used as a statistical test. Results The Results showed that 52 respondents (75%) had introverted personality types, with the mayority of good caring behaviour 67 people (97,1%). The results showed that personality types were not related to caring behaviour (p-value = 0,402 ; p >0,05), which means Ho is rejected. Conclusion : There is no relationship between personalty type and caring behaviour of nurses.